A kind of degradable adhesive and preparation method thereof

By using raw materials such as corn starch and aminated dextran, a degradable adhesive with simple process and excellent performance was prepared, which solved the problems of complex preparation and insufficient performance of existing oxidized starch adhesives, and achieved efficient wood bonding and green environmental protection.

CN115678457BActive Publication Date: 2025-04-11GUANGXI ZHISHAN NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211474136.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-04-11
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

The preparation process of existing oxidized starch adhesives is complex, and the adhesive's stability, adhesion, water resistance and other properties are insufficient, making it difficult to widely use on wood and other materials.

Method used

The raw materials such as corn starch, aminated dextran, oxidant, water, sodium oxyoxide, defoaming agent, crosslinking agent, acid and aluminum sulfate are prepared through simple stirring and mixing steps to enhance its adhesion and water resistance.

Benefits of technology

It improves the adhesion, water resistance and stability of the adhesive, simplifies the preparation process, reduces production costs, imparts green and degradable properties to the adhesive, and is suitable for bonding of wood and other materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003957690750000081
    Figure BDA0003957690750000081
  • Figure BDA0003957690750000092
    Figure BDA0003957690750000092
  • Figure BDA0003957690750000101
    Figure BDA0003957690750000101
Patent Text Reader

Abstract

The present invention provides a degradable adhesive and a preparation method thereof. The preparation method of the degradable adhesive of the present invention, by introducing the hydrogen bonding between the hydroxyl group and the amino group on the oxidized corn starch and the oxidized waxy corn starch, on the one hand, enhances the bonding force, and on the other hand, because the amino group has strong hydrophilicity, it can protect the corn starch molecular chain, thereby weakening the influence of water molecules on the oxidized waxy corn starch adhesive, and improving the water resistance; the corn starch is oxidized by a simple oxidant to introduce aldehyde groups and carboxyl groups, thereby improving the overall stability of the adhesive; at the same time, the oxidation also reduces the polymerization degree of corn starch to a certain extent, and the degradation of the long molecules of corn starch leads to the formation of relatively short molecular chains, which enhances the fluidity of the oxidized corn starch adhesive and improves the processing performance; the amino glucan is a biodegradable high molecular polymer, and the combination with the oxidized corn starch gives the adhesive green degradable properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to a degradable adhesive and a preparation method thereof. Background Art

[0002] Traditional adhesives produce various harmful substances, such as formaldehyde, during the production and processing process. Because a large amount of organic solvents are used for the reaction, the processing environment is not good for the human body, and the adhesives after use face the problems of difficult cleaning and degradation. In order to solve the problem of green and environmentally friendly adhesives, adhesives with starch as raw materials have emerged. Starch can be obtained from various plants and crops, such as corn, sweet potatoes, red beans, mung beans, potatoes, etc. It has abundant sources, large reserves, low costs, and has objective research and development prospects. However, the use of starch as a raw material for adhesives faces problems such as poor stability, weak adhesion, and weak water resistance. Stability is related to the preparation conditions. There are two main methods for starch glue: cold processing and hot processing. The main preparation process is simple gelatinization. The hot processing time is short, while the cold processing starch glue can be stored for a long time. The bonding force of starch adhesives mainly depends on the hydroxyl groups in the starch chain. Hydrogen bonds are formed between the hydroxyl groups to achieve the purpose of bonding between the materials. However, the bonding force provided by the action between the hydroxyl groups is insufficient, so it is rare to use starch adhesives on wood. Since water molecules also have cohesive forces with hydroxyl groups, they will enter the starch glue, thus weakening the adsorption between the starch glue and the bonding material. If the hydrogen bond force is too strong, it will restrict the movement of the starch chain segments, reduce the fluidity of the colloid, and be unfavorable for construction.

[0003] The prior art discloses a preparation method and a use method of a cross-linked hyperbranched amine-modified oxidized starch adhesive for gluing wood. That is, corn starch is oxidized by ammonium persulfate to introduce new functional groups, thereby improving the stability of adhesion to the material. The oxidation process uses instruments and equipment such as a four-necked flask, a spherical condenser, and a thermometer. The cross-linking between the oxidized starch molecular chains is mainly through trimesoyl chloride and hyperbranched amines. First, trimesoyl chloride reacts with the hydroxyl group of starch to be grafted onto the oxidized starch, and then the hyperbranched amine reacts with the acyl chloride group to be grafted onto the oxidized starch to obtain a hyperbranched amine-modified oxidized starch adhesive. However, the preparation method is complex.

[0004] Based on the defects in the preparation of current oxidized starch adhesives, it is necessary to improve this Summary of the invention

[0005] In view of this, and in view of the above-mentioned deficiencies in the prior art, the present invention provides a degradable adhesive and a preparation method thereof.

[0006] In a first aspect, the present invention provides a degradable adhesive comprising the following raw materials in parts by weight: 40 to 60 parts of corn starch, 10 to 50 parts of aminodextran, 35 to 40 parts of oxidant, 160 to 200 parts of water, 5 to 6 parts of sodium oxychloride, 2 to 4 parts of defoaming agent, 1 to 4 parts of cross-linking agent, 5 to 10 parts of acid, and 0.2 to 0.4 parts of aluminum sulfate.

[0007] Preferably, in the degradable adhesive, the oxidant is hydrogen peroxide;

[0008] and / or, the defoaming agent comprises at least one of polydimethylsiloxane or tributyl phosphate;

[0009] And / or, the cross-linking agent includes at least one of borax, citric acid, and sodium trimetaphosphate;

[0010] And / or, the acid is glacial acetic acid.

[0011] In a second aspect, the present invention further provides a method for preparing the degradable adhesive, comprising the following steps:

[0012] Add corn starch to water, stir, and then add an oxidant to cause an oxidation reaction to obtain oxidized corn starch;

[0013] Add oxidized corn starch and amino glucan into water, stir to mix, then add sodium hydroxide and defoamer, continue stirring, add water and stir again, then add cross-linking agent and aluminum sulfate, stir, add acid to adjust pH, and obtain a degradable adhesive.

[0014] Preferably, in the method for preparing the degradable adhesive, the oxidant is hydrogen peroxide, and the mass concentration of the hydrogen peroxide is 27-35%.

[0015] Preferably, in the method for preparing the degradable adhesive, acid is added to adjust the pH to 4.5-5.

[0016] Preferably, in the method for preparing the degradable adhesive, oxidized corn starch and aminodextran are added to water and stirred and mixed at 35-45°C.

[0017] Preferably, in the preparation method of the degradable adhesive, oxidized corn starch and aminodextran are added to water, stirred and mixed at 35-45° C., and then sodium hydroxide and defoaming agent are added, and stirring is continued for not less than 30 minutes before adding water and stirring again.

[0018] Preferably, in the method for preparing the degradable adhesive, corn starch is added to water, stirred, and then an oxidant is added to cause an oxidation reaction, followed by filtering, washing, and drying to obtain oxidized corn starch.

[0019] Preferably, in the preparation method of the degradable adhesive, the drying temperature is 40-60°C.

[0020] Preferably, in the method for preparing the degradable adhesive, the weight average molecular weight of the aminodextran is 90,000-110,000.

[0021] The degradable adhesive and preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0022] The preparation method of the degradable adhesive of the present invention comprises the following steps: on one hand, the bonding force is enhanced by introducing the hydrogen bonding between the hydroxyl group and the amino group on the oxidized corn starch and the oxidized waxy corn starch; on the other hand, the amino group has strong hydrophilicity and can protect the corn starch molecular chain, thereby reducing the influence of water molecules on the oxidized waxy corn starch adhesive and improving the water resistance; the corn starch is oxidized by a simple oxidant to introduce aldehyde groups and carboxyl groups, thereby improving the overall stability of the adhesive; at the same time, the oxidation also reduces the polymerization degree of the corn starch to a certain extent, and the degradation of the long molecules of the corn starch leads to the formation of relatively short molecular chains, thereby enhancing the fluidity of the oxidized corn starch adhesive and improving the processing performance; the amino glucan is a biodegradable high molecular polymer, and the combination with the oxidized corn starch gives the adhesive green and degradable performance; the addition of aluminum sulfate can be complexed with the starch to increase the viscosity of the adhesive; the preparation method of the degradable adhesive of the present invention has simple process, short time consumption, high economic benefit and meets the basic requirements of industrial production. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The embodiment of the present application provides a degradable adhesive, comprising the following raw materials in parts by weight: 40-60 parts of corn starch, 10-50 parts of aminodextran, 35-40 parts of oxidant, 160-200 parts of water, 5-6 parts of sodium oxychloride, 2-4 parts of defoaming agent, 1-4 parts of cross-linking agent, 5-10 parts of acid, and 0.2-0.4 parts of aluminum sulfate.

[0025] In some embodiments, the oxidizing agent is hydrogen peroxide;

[0026] and / or, the defoaming agent comprises at least one of polydimethylsiloxane or tributyl phosphate;

[0027] and / or, the cross-linking agent comprises at least one of borax (i.e., sodium borate), citric acid, and sodium trimetaphosphate;

[0028] And / or, the acid is glacial acetic acid.

[0029] Based on the same inventive concept, the present application also provides a method for preparing the above-mentioned degradable adhesive, comprising the following steps:

[0030] S1. Add corn starch to water, stir, and then add an oxidant to cause an oxidation reaction to obtain oxidized corn starch;

[0031] S2. Add oxidized corn starch and amino glucan into water, stir to mix, then add sodium hydroxide and defoamer, continue stirring, add water and stir again, then add cross-linking agent and aluminum sulfate, stir, add acid to adjust pH, and obtain a degradable adhesive.

[0032] The preparation method of the degradable adhesive of the present invention has abundant corn starch sources, and the hydrogen peroxide used as the oxidant will decompose into water and oxygen. The oxidation process is simple to operate and is green and environmentally friendly. The oxidation of corn starch mainly occurs on the hydroxyl group on the glucose unit C6 of the starch. The oxidation introduces aldehyde groups and carboxyl groups, which reduces the degree of polymerization of corn starch to a certain extent. The degradation of long molecules of corn starch leads to the formation of relatively short molecular chains, which enhances the movement of oxidized corn starch molecular chains. The introduction of aldehyde groups and carboxyl groups can improve the bonding ability to paper fibers, and can also improve stability and anti-corrosion performance. Glucan is a biodegradable high molecular polymer that can be degraded into low molecular sugars. The hydrogen bonding between the hydroxyl group and the amino group on the amino-glucan and the oxidized corn starch can enhance the bonding force on the one hand, and weaken the influence of water molecules on the oxidized corn starch adhesive on the other hand. The amino group has strong hydrophilicity and can protect the corn starch molecular chain.

[0033] In some embodiments, the oxidant is hydrogen peroxide, and the mass concentration of hydrogen peroxide is 27-35%.

[0034] In some embodiments, acid is added to adjust the pH to 4.5-5.

[0035] In some embodiments, oxidized corn starch and aminodextran are added to water and stirred and mixed at 35-45°C.

[0036] In some embodiments, oxidized corn starch and aminodextran are added to water, stirred and mixed at 35-45° C., and then sodium hydroxide and defoaming agent are added. After stirring for at least 30 minutes, water is added and stirred again.

[0037] In some embodiments, corn starch is added to water, stirred, and then an oxidant is added to produce an oxidation reaction, followed by filtering, washing, and drying to obtain oxidized corn starch.

[0038] In some embodiments, the drying temperature is 40-60°C.

[0039] In some embodiments, the weight average molecular weight of the amino dextran is 90,000-110,000.

[0040] In some embodiments, all stirring during the preparation process is magnetic stirring, stirring during the corn oxidation process is carried out at room temperature, and the stirring temperature during the preparation process of the oxidized waxy corn starch adhesive is 40°C water bath temperature; the oxidized corn starch is added in the form of powder; the aminodextran is added in the form of powder or aqueous solution; the cross-linking agent is added in the form of aqueous solution; the defoaming agent is added in the form of an aqueous solution; aluminum sulfate is added in the form of an aqueous solution; and the oxidized corn starch is dried in a controlled vacuum drying oven or a forced air drying oven.

[0041] In some embodiments, the amino-dextran has a weight average molecular weight Mw of 100,000 and a product number of ZCR-DE-665 (produced by Creative PEGWorks, USA).

[0042] In some embodiments, the sodium hydroxide solution used is sodium hydroxide solution with a mass concentration of 25-35%.

[0043] The preparation method of the degradable adhesive of the present application has the following advantages:

[0044] The preparation method of the degradable adhesive of the present application has a simple preparation process, does not require the use of complex instruments and equipment, has mild processing conditions, does not require complex reactions, and is green and environmentally friendly; the present application introduces aminoglucan into the hydroxyl group on the oxidized corn starch and the hydrogen bonding between the amino group and the oxidized glutinous corn starch to enhance the bonding force on the one hand, and on the other hand, since the amino group has strong hydrophilicity, it can protect the corn starch molecular chain, thereby weakening the influence of water molecules on the oxidized glutinous corn starch adhesive and improving water resistance; corn starch is oxidized by a simple oxidant to introduce aldehyde and carboxyl groups, thereby improving the overall stability of the adhesive; at the same time, oxidation also reduces the polymerization degree of corn starch to a certain extent, and the degradation of the long molecules of corn starch leads to the formation of relatively short molecular chains, thereby enhancing the fluidity of the oxidized corn starch adhesive and improving the processing performance; aminoglucan is a biodegradable high molecular polymer, and the combination with oxidized corn starch gives the adhesive green and degradable properties; the addition of aluminum sulfate can be complexed with starch to increase the viscosity of the adhesive.

[0045] The following further illustrates the degradable adhesive of the present application and its preparation method with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means adopted in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The weight-average molecular weight Mw of the aminoglucan used in the following examples and comparative examples is 100,000, and the item number is ZCR-DE-665 (produced by Creative PEGWorks, USA); corn starch was purchased from Heilongjiang Haotian Corn Development Co., Ltd.

[0046] Example 1

[0047] The present invention provides a method for preparing a degradable adhesive, comprising the following steps:

[0048] S1. Add 50 g corn starch to 80 mL of water and stir to dissolve, then add 40 mL of 27.5% hydrogen peroxide solution, stir evenly, filter, wash and dry to obtain oxidized corn starch;

[0049] S2. After mixing the oxidized corn starch obtained in step S1 and 5 g of amino-dextran, add 40 mL of water and stir evenly at 40° C., then add 5 mL of 30% sodium hydroxide solution and 2 mL of polydimethylsiloxane, stir for 35 min, add 40 mL of water and continue stirring for 25 min, then add 1 mL of borax solution (mass concentration is 10%) and 10 mL of aluminum sulfate solution (the preparation method of aluminum sulfate solution is: add 0.2 g of aluminum sulfate to 10 mL of water), stir, add acetic acid to adjust the pH to 5, and obtain a degradable adhesive.

[0050] Example 2

[0051] The present invention provides a method for preparing a degradable adhesive, comprising the following steps:

[0052] S1. Add 50 g corn starch to 80 mL of water and stir to dissolve, then add 40 mL of 27.5% hydrogen peroxide solution, stir evenly, filter, wash and dry to obtain oxidized corn starch;

[0053] S2. After mixing the oxidized corn starch obtained in step S1 and 10 g of amino-dextran, add 40 mL of water and stir evenly at 40° C., then add 5 mL of 30% sodium hydroxide solution and 2 mL of polydimethylsiloxane, stir for 35 min, add 40 mL of water and continue stirring for 25 min, then add 1 mL of borax solution (mass concentration is 10%) and 10 mL of aluminum sulfate solution (the preparation method of aluminum sulfate solution is: add 0.2 g of aluminum sulfate to 10 mL of water), stir, add acetic acid to adjust the pH to 5, and obtain a degradable adhesive.

[0054] Example 3

[0055] The present invention provides a method for preparing a degradable adhesive, comprising the following steps:

[0056] S1. Add 50 g corn starch to 80 mL of water and stir to dissolve, then add 40 mL of 27.5% hydrogen peroxide solution, stir evenly, filter, wash and dry to obtain oxidized corn starch;

[0057] S2. After mixing the oxidized corn starch obtained in step S1 and 15 g of amino-dextran, add 40 mL of water and stir evenly at 40° C., then add 5 mL of 30% sodium hydroxide solution and 2 mL of polydimethylsiloxane, stir for 35 min, add 40 mL of water and continue stirring for 25 min, then add 1 mL of borax solution (mass concentration is 10%) and 10 mL of aluminum sulfate solution (the preparation method of aluminum sulfate solution is: add 0.2 g of aluminum sulfate to 10 mL of water), stir, add acetic acid to adjust the pH to 5, and obtain a degradable adhesive.

[0058] Example 4

[0059] The present invention provides a method for preparing a degradable adhesive, comprising the following steps:

[0060] S1. Add 50 g corn starch to 80 mL of water and stir to dissolve, then add 40 mL of 27.5% hydrogen peroxide solution, stir evenly, filter, wash and dry to obtain oxidized corn starch;

[0061] S2. After mixing the oxidized corn starch obtained in step S1 and 20 g of aminodextran, add 40 mL of water and stir evenly at 40° C., then add 5 mL of 30% sodium hydroxide solution and 2 mL of polydimethylsiloxane, stir for 35 min, add 40 mL of water and continue stirring for 25 min, then add 1 mL of borax solution (mass concentration is 10%) and 10 mL of aluminum sulfate solution (the preparation method of aluminum sulfate solution is: add 0.2 g of aluminum sulfate to 10 mL of water), stir, add acetic acid to adjust the pH to 5, and obtain a degradable adhesive.

[0062] Example 5

[0063] The present invention provides a method for preparing a degradable adhesive, comprising the following steps:

[0064] S1. Add 50 g corn starch to 80 mL of water and stir to dissolve, then add 40 mL of 27.5% hydrogen peroxide solution, stir evenly, filter, wash and dry to obtain oxidized corn starch;

[0065] S2. After mixing the oxidized corn starch obtained in step S1 and 25 g of amino-dextran, add 40 mL of water and stir evenly at 40° C., then add 5 mL of 30% sodium hydroxide solution and 2 mL of polydimethylsiloxane, stir for 35 min, add 40 mL of water and continue stirring for 25 min, then add 1 mL of borax solution (mass concentration is 10%) and 10 mL of aluminum sulfate solution (the preparation method of aluminum sulfate solution is: add 0.2 g of aluminum sulfate to 10 mL of water), stir, add acetic acid to adjust the pH to 5, and obtain a degradable adhesive.

[0066] Comparative Example 1

[0067] This comparative example provides a method for preparing an adhesive, comprising the following steps:

[0068] S1. Add 50 g corn starch to 80 mL of water and stir to dissolve, then add 40 mL of 27.5% hydrogen peroxide solution, stir evenly, filter, wash and dry to obtain oxidized corn starch;

[0069] S2. Add 40 mL of water to the oxidized corn starch obtained in step S1, stir evenly at 40° C., then add 5 mL of 30% sodium hydroxide solution and 2 mL of polydimethylsiloxane, stir for 35 min, add 40 mL of water and continue stirring for 25 min, then add 1 mL of borax solution (mass concentration is 10%) and 10 mL of aluminum sulfate solution (the preparation method of aluminum sulfate solution is: add 0.2 g of aluminum sulfate to 10 mL of water), stir, add acetic acid to adjust the pH to 5, and obtain an adhesive.

[0070] Performance Testing

[0071] Mechanical properties test

[0072] The adhesives prepared in Examples 1 to 5 and Comparative Example 1 were poured into a rectangular polytetrafluoroethylene mold, dried at 60°C to form a film, and then hot-pressed on a flat vulcanizer for 1 min (hot-pressing temperature was 120°C and pressure was 5 MPa), and then cut into samples. A tensile test was performed on the prepared adhesive samples at room temperature using a universal tester to test the tensile strength and elongation at break of the samples, and the results are shown in Table 1 below.

[0073] Table 1 - Mechanical properties of adhesives obtained from different embodiments

[0074]

[0075]

[0076] It can be seen from Table 1 that the tensile strength of the adhesive in Comparative Example 1 is the smallest, while the tensile strengths of the adhesives in Examples 1 to 5 are all above 8 MPa, indicating that with the increase of amino glucan, the mechanical properties of the adhesive are improved.

[0077] Tensile shear strength test

[0078] Take 1mL of the adhesive prepared in Examples 1 to 5 and Comparative Example 1 and evenly apply it on oak, polypropylene and polytetrafluoroethylene, respectively, control the thickness of the adhesive layer to be 0.2mm, take out the same substrate on the other side (i.e. oak, polypropylene and polytetrafluoroethylene) and fix it with it, the overlap size is 25mm×25mm, and obtain a bonding sample. The bonding sample is placed in an oven at 60 degrees Celsius for drying. After drying, cool at room temperature, use a stretching machine to perform a shear strength test, the stretching rate is 5mm / min, and the shear strength is obtained, as shown in Table 2.

[0079] Table 2- Shear strength of adhesives obtained in different embodiments

[0080]

[0081] It can be seen from Table 2 that all adhesives have greater shear strength on oak wood, and the adhesives in Examples 1 to 5 have greater shear strength than Comparative Example 1.

[0082] Degradation performance test

[0083] The adhesive prepared in Example 2 and Comparative Example 1 was poured into a rectangular polytetrafluoroethylene mold, dried at 60°C to form a film, cut into 4cm×4cm, and dried to constant weight. After weighing m0 on an electronic balance, it was buried in the soil rich in microorganisms in the woods to a depth of about 20cm. To maintain soil moisture, deionized water was regularly added to the buried area to moisten it; it was taken out every 2 weeks, rinsed and dried, and weighed m. The degradation rate was calculated according to the following formula:

[0084] Degradation rate W = (m0-m) / m0.

[0085] According to the above method, the degradation rates of the adhesives prepared in Example 2 and Comparative Example 1 were tested respectively, and the results are shown in Tables 3 to 4 below.

[0086] Table 3 - Adhesive degradation rate in Example 2

[0087]

[0088] Table 4-Adhesive degradation rate in comparative example 1

[0089]

[0090] It can be seen from Table 3 and Table 4 that the final degradation rate of the adhesive in Example 2 is 5.69%, while the adhesive in Comparative Example 1 only degrades less than 2% after 14 weeks under the same conditions. It can be seen that the degradation performance of the adhesive in Example 2 is much higher than that of Comparative Example 1. It can be seen that the adhesive prepared in this application has excellent biodegradability.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a degradable adhesive, characterized in that: The following steps are involved: S1. Add 50 g corn starch to 80 mL of water and stir to dissolve, then add 40 mL of 27.5% hydrogen peroxide solution, stir evenly, filter, wash and dry to obtain oxidized corn starch; S2, after mixing the oxidized corn starch and aminoglucan obtained in step S1, add 40 mL of water and stir evenly at 40° C., then add 5 mL of 30% sodium hydroxide solution and 2 mL of polydimethylsiloxane, stir for gelatinization for 35 min, add 40 mL of water and continue stirring for 25 min, then add 1 mL of 10% borax solution and 10 mL of aluminum sulfate solution, stir, and then add acetic acid to adjust the pH to 5, to obtain a degradable adhesive; The aluminum sulfate solution is prepared by adding 0.2 g of aluminum sulfate to 10 mL of water; The added mass of amino-dextran is any one of 5g, 10g, 15g, 20g and 25g.

2. The method for preparing a degradable adhesive according to claim 1, wherein: 50 g corn starch was added to 80 mL of water and stirred to dissolve, and then 40 mL of a hydrogen peroxide solution with a mass concentration of 27.5% was added, and after stirring evenly, the mixture was filtered, washed, and dried to obtain oxidized corn starch at a drying temperature of 40 to 60°C.

3. The method for preparing a degradable adhesive according to claim 1, wherein: The weight average molecular weight of the amino-dextran is 90,000-110,000.

Citation Information

Patent Citations

  • Method for preparing modified starch cigarette adhesive

    CN106634687A

  • Oxidized corn starch adhesive and preparation method thereof

    CN110804405A